Delegate and Verify the Update Keys of Revocable Identity-Based Encryption - Kwangsu Lee (IEEE Access, 2023)
Revocable identity-based encryption (RIBE) is an extension of identity-based encryption (IBE) and it supports efficient revocation of private keys. In the past, many efficient RIBE schemes have been proposed, but research on efficiently delegating the generation of update keys to a cloud server is somewhat insufficient. In this paper, we newly introduce the concept of delegated RIBE (DRIBE) that can delegate the generation of update keys to the semi-trusted cloud server and define the security models of DRIBE. Next, we propose a DRIBE scheme by generically combining a hierarchical IBE (HIBE) scheme, an identity-based broadcast encryption (IBBE) scheme, and a collision-resistant hash function. In addition, we propose a DRIBE-INC scheme that generates an occasional base update key and a periodic incremental update key to reduce the size of update keys in our DRIBE scheme.